Effect of Different Substrate Temperature on Sb-Doped ZnO Thin Films Prepared by Pulsed Laser Deposition on Sapphire Substrates - 赵子文 胡礼中 张贺秋 孙景昌 边继明 孙开通 陈希 赵涧泽 李雪 朱锦霞 (Chinese physics letters, 2010)
Sb-doped ZnO thin films are deposited on c-plane sapphire substrates by pulsed laser deposition. Hall results indicate that the conductivity of the Sb-doped ZnO thin films is strongly dependent on the substrate temperature. The sample deposited at the temperature of 550°C exhibits p-type conductivity. It gives a resistivity of 15.25Ω＆#12539;cm, with a Hall mobility of 1.79cm2V-1s-1 and a carrier concentration of 2.290×1017cm-3 at room temperature. The x-ray diffraction indicates that the Sb-doped ZnO thin films deposited in the range of 450-650°C are high c-axis oriented. Low-temperature photoluminescence spectra indicate that the sample deposited at 550°C shows the strong acceptor-bound exciton （A0X） emission.